Estudio sobre la aplicación de la Teoría del Trabajo Social a su práctica diaria - Barrera Algarín, Evaristo; Malagón Bernal, José Luis; SARASOLA SÁNCHEZ-SERRANO, José Luis (Cuadernos de Trabajo Social, 2009)
This article is the result of a recent study (Researched by the Research Group PAI SEJ-452, dedicated to the study of Social Work and Social Policies. University Pablo de Olavide in Seville, Spain.) of social workers from both private and public sectors that was conducted in the province of Seville and completed in June 2007. The study focuses on the relationship that exists between theoretical knowledge possessed by social workers’ and its actual usefulness when applied to their everyday work. The research essentially utilizes quantitative research methodology to analyze elements typical of social workers’ labour context, their professional profiles, intervention sectors, most common tasks, their relationship with the organisation, subjective perception of their work as well as the intervention models used most. Interviews were also conducted to obtain information of a higher quality. The authors explore the theory/practice dualism in Social Work as a discipline and its connection with welfare models.
Keywords: Social work; Methodology; Intervention models; Theory-practice